2021
DOI: 10.7759/cureus.18813
|View full text |Cite
|
Sign up to set email alerts
|

A Foreign Body in the Cephalic Vein: Broken Piece of Intravenous Cannula

Abstract: Peripheral intravenous cannulation is a routine in the medical field with the rarity of complications in expert hands. However, at times, complications arise including the fracture of the cannula inside the vein, which is a rare but potentially serious complication with the possibility of pulmonary embolism. We have reported a case of a broken piece of a cannula in the cephalic vein removed with the help of a Fogarty catheter with the emphasis on preoperative imaging studies to localize it and use of a tourniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…Most intravascular foreign bodies are iatrogenic, and these include cannulas, stents, and needles among others. 5 6 Posttraumatic intravenous foreign bodies are uncommon, and their migration to the thoracic cavity has an estimated 2% mortality rate. 1 Migrating foreign bodies are more common in the military or civilian setting after penetrating firearm injuries or explosions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most intravascular foreign bodies are iatrogenic, and these include cannulas, stents, and needles among others. 5 6 Posttraumatic intravenous foreign bodies are uncommon, and their migration to the thoracic cavity has an estimated 2% mortality rate. 1 Migrating foreign bodies are more common in the military or civilian setting after penetrating firearm injuries or explosions.…”
Section: Discussionmentioning
confidence: 99%
“… 1 2 In our case, the foreign body was superficial and had not migrated, but should the access become more difficult minimally invasive endovascular techniques with special snares, loops, baskets, and other instruments have been described with favorable outcomes and minimal morbidity to the patient. 6 …”
Section: Discussionmentioning
confidence: 99%
“…Most reports in the literature of intravenous foreign bodies are that of needles, stents, catheters, or other iatrogenically placed hardware 1,2 . Although traumatic intravenous foreign bodies have been reported on occasion, these case reports are largely made up of metal shrapnel fragments measuring less than 5 mm [4][5][6] .…”
Section: Discussionmentioning
confidence: 99%
“…ntravascular foreign bodies are uncommon occurrences that are typically iatrogenic secondary to failed hardware including stents, cannulas, needles, and catheters [1][2][3] . Most intravascular foreign bodies have been found in the arterial system, and venous foreign bodies after a trauma have rarely been reported in the literature [4][5][6] .…”
mentioning
confidence: 99%
“…Iatrogenic foreign bodies, such as an intravenous cannula or venous catheter fragments, are the most common causes of intravascular foreign bodies. 2,[5][6][7][8][9][10] Moreover, embolization that occurs as a result of penetrating injuries, such as gunshot wounds or industrial accidents, have been reported. 10 Bypareddy et al reported a metallic foreign body-induced post-traumatic occlusion of the superotemporal branch of the retinal blood vessel.…”
mentioning
confidence: 99%